The United States legitimization and justification of the Iraq invasion in 2003 under international law - Gnashuk, Mariia (Riga Graduate School of Law, 2021)
Prior to the 2003 invasion of Iraq by United States and its partners, Iraq failed to fully comply with some of the obligations posed by the UN Security Council resolutions 1441 and 687. Under the Bush administration, it is widely believed that United States' main objectives were to remove Saddam Hussein from power, remove possible threats such as Saddam Hussein’s possession of WMD, and stop Iraq from supporting terrorist groups, and because of economic reasons. It is still unclear whether the invasion of Iraq was permitted under International law. This paper will examine UN Charter articles and Security Council resolutions to evaluate the legitimacy of the invasion.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Iraq war